Empty Aluminium Honeycomb under Quasi-Static Loading: Experiment and Simulation - Chuli, A.J.; Said, M.R.; Pokaad, A.Z. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
In recent years, study involving aluminium honeycomb has grown rapidly. This is due to the properties of aluminium honeycomb that are very useful in energy absorbing area. This paper focuses on compressing the aluminium honeycomb in all directions; in-plane and out-of-plane direction for both experimental and simulation work. It is found that compression in out-of-plane direction offered far superior energy absorbing characteristic compared to the in-plane directions. Factor that contributes to this difference is found to be the imperfection of the aluminium honeycomb itself. All honeycomb deformed dissimilarly base on the stiffness and direction of compression.